Faktor-Faktor yang Mempengaruhi Kegagalan Pemberian ASI Eksklusif pada Ibu dengan Bayi 6-12 Bulan di RSIA Murni Teguh - Masriayanti Berutu; Sridama Yanti Harahap (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The World Health Organization (WHO) stated that the prevalence of exclusive breastfeeding data globally, although there has been an increase, has not increased significantly, which is around 44% of the target of 50%. Factors suspected of influencing failure are knowledge, perception, family support, and employment. Objective: To determine the factors influencing the failure of exclusive breastfeeding in mothers with babies aged 6-12 months. Method: This type of research is descriptive analytical using the cross-sectional method. The study was conducted at RSIA Murni Teguh Rosiva Medan. The population was 62 people and all of them were used as samples (total sampling). Sampling was done by purposive sampling. The data used were primary data and secondary data. The analysis was conducted univariately and bivariately using the Chi-Square test. Results: Factors that influence the failure of exclusive breastfeeding at the Murni Teguh Rosiva Mother and Child Hospital Medan are perception (p = 0.000 <0.05), family support (p = 0.015 <0.05), and work (p = 0.032 <0.05), while the knowledge variable has no effect (p = 0.654 > 0.05). Conclusion: perception, support, family and work influence the failure of exclusive breastfeeding. Suggestion: It is recommended that nurses at the Murni Teguh Rosiva Medan Hospital encourage new mothers to only give breast milk to their babies until they are 6 months old